Project-Based Curriculum Development to Enhance Students' Skills - Wedia Hastuti; Astuti Salim; Irianto M.Ali; Mirna Riazil Jannah; Arifannisa (CV. Get Press Indonesia, 2025)
This study develops, implements, and evaluates a Project-Based Curriculum (PjBC) model to enhance core 21st-century skills: critical thinking, collaboration, communication, and time management. Using a Research and Development (R&D) mixed-methods approach following the ADDIE Model, the curriculum was tested with approximately 35 tenth-grade students at an urban high school. Quantitative skill assessments showed overall effectiveness, with Critical Thinking scoring 82.5%, Collaboration 80.7%, and Communication 78.3%. Time Management presented the primary challenge at 68.4%. The study's innovation integrates continuous teacher coaching and a structured Micro-Milestone strategy within the PjBC framework to address common implementation barriers. Findings emphasize robust teacher support and explicit project guidance for comprehensive 21st-century skill development, offering policymakers a validated model aligned with global competency standards.​